Transformation of Islamic Economic Politics in Indonesia: A Study of Developments in the New Order Era - Deviana putri septia ningrum; Veni Vebriyanti; Siti Aisyah Hidayatul Hasanah; Mashudi (Al-Abqori: Journal of Islamic Thought Studies, 2025)
The. transformation of Islamic e.conomic politics in Indone.sia, e.spe.cially in the. Ne.w Orde.r e.ra, is an inte.re.sting phe.nome.non to study. With the. large.st Muslim population in the. world, Indone.sia has significant pote.ntial in de.ve.loping Islamic e.conomics as an inte.gral part of the. national financial and e.conomic syste.m. In this study, the. author use.s a qualitative. de.scriptive. writing me.thod and use.s a lite.rature. study. The. re.sults of this study and the. conclusions of this study are. that the. transformation of Islamic e.conomic politics in Indone.sia has shown positive. de.ve.lopme.nts. Although in its re.alization and proce.ss the.re. are. still many obstacle.s. Support from the. Gove.rnme.nt is ne.e.de.d through re.gulations as we.ll as be.ing a pione.e.r for national community move.me.nts and political support from the. community with the. aware.ne.ss of using halal products and carrying out e.conomic activitie.s that use. sharia principle.s so that it is hope.d that the. Islamic e.conomy in Indone.sia will continue. to de.ve.lop in the. future..